Peniadaan Hak Waris Anak Perempuan Pada Kewarisan Adat Bali Perspektif Hukum Waris Islam; Studi Kasus di Desa Tegallinggah Kecamatan Sukasada Kabupaten Buleleng - Latif Rahman; Nashrun Jauhari (Saintifika Islamica, 2022)
This journal discusses how to eliminate the inheritance rights of girls in traditional Balinese inheritance (in Tegallinggah Village, Sukasada District, Buleleng Regency) How to Review Islamic Law Against the abolition of girls' inheritance rights in Balinese traditional inheritance (in Tegallinggah Village, Kec. Sukasada, Buleleng Regency). This study uses an empirical juridical approach. This approach aims to understand that the law is not merely a set of statutory rules that are normative in nature, but the law is understood as the behavior of the people who are symptomatic in their lives. from generation to generation, from men in power over the assets left behind as a result of the consequences of the distribution system, the absence of inheritance rights for girls due to lack of community knowledge and having long used local customary law makes Islamic inheritance law difficult to apply to Muslim families in Tegallinggah Village, Kec. Sukasada, Kab. Buleleng.